Laccase-mimicking Cu@CDs-enabled bioinspired immunosensor using CuO nanoparticles for voltametric detection of serum thyroxine level in patients with hyperthyroidism or hypothyroidism - Mohammad Ali Farzin; Seyed Morteza Naghib (Sensors and Actuators Reports)
In this study, for the first time, a voltammetric bioinspired immunosensor was fabricated to determine free thyroxine (T4) based on the blocking nanozyme-dependent signaling pathway through masking the active sites of the laccase-mimicking Cu-doped CDs (Cu@CDs). The focus shifted to monitoring a vital biomarker for thyroid diseases using a metal-containing nanozyme, showcasing high potential to catalyze the oxidation of phenolic compounds. Thanks to the active sites of Cu@CD nanozyme, the electrocatalytic oxidation of hydroquinone (HQ), as a signal probe, was performed at a high rate. The CuO nanostructures also increased the conductivity as well as specific surface area of electrode. Despite signal amplification of HQ, the binding of antibody to carbon dot reduced enzymatic activity of nanozyme and subsequently resulted in a considerable decrease in the current intensity of GCE/CuO nanoparticles/Cu@CDs-HQ. The bioconjugation of T4 with anti-T4 antibody resulted in the further coverage of the active sites of nanozyme. Therefore, the current of GCE/CuO nanoparticles/Cu@CDs-HQ/Ab decreased proportionally to the T4 concentration in a DLR (dynamic linear range) of 10.0 pM-8.0 nM which comprises the reference range for free T4 (11.5–22.7 pM). The LOD (limit of detection) of 2.8 pM, was lower compared to the values reported in previous studies. Furthermore, this study exhibited the key finding that the highly specific interaction of T4 with immobilized antibody led to a remarkable diminish in the immunosensor signal compared to the interferers. More importantly, spike-recovery studies demonstrated the high potential of the designed immunosensor to detect serum T4 levels in patients with hyperthyroidism or hypothyroidism.